Suspension of the exercise of the rights to freedom of transit and assembly in the context of the covid-19 pandemic: general standards provided by the Mexican constitutional block - Hernández-López, Luís Ernesto (DIXI, 2022)
The sars-CoV-2 pandemic (covid-19) has posed a challenge not only to the social, health and economic system of the Mexican State, but also to its respective legal system and to the guarantee of human rights recognized by its fundamental Charter in favor of all persons. In order to guarantee security, health and the containment of the virus, the different levels of political organization (federal, state and municipal) have opted for the issuance of measures that affect the full enjoyment and exercise of prerogatives such as freedom of assembly and transit. However, in order for those measures to be considered legitimate, they must be carried out within the framework of an exceptional situation for the life of a country; and comply with the requirements and normative standards provided by article 29 of the Political Constitution of the United Mexican States, as well as by ordinal 27 of the American Convention on Human Rights. General conditions that we will address in accordance with the criteria established in the Inter-American jurisprudence, from a teleological perspective of those precepts, with the intention of elucidating the legal and social context in which the referred freedoms would be susceptible to suspension.